PEMBERIAN DUAL TASK EXERCISE DAN EDUKASI UNTUK MENCEGAH PENURUNAN FUNGSI KOGNITIF PADA LANSIA DI DESA NAMBO - Setyaningsih, Dinda Biolawatika; Agustina, Dwi; Sudarsono, Ari; Magdalena, Maria; Aulia Rijaldi, Muhammad; Nur Putri, Nabila; Aristawati, Nurul Izzah; Winda Yanznur, Sulistyanti; Nur Afifah, Wafiq Khoirunnisa (IFI cabang Kota Bekasi, 2024)
Background: Elderly is someone who has reached the age of 60 (sixty) years and above. The elderly are characterized by physiological decline, one of which is a decline in cognitive function. Cognitive function is a high-level function of the human brain which consists of several aspects such as visual perception and the construction of numeracy skills, perception and use of language, information processing, memory, executive function and problem solving. If cognitive dysfunction occurs, it can interfere with daily activities. A positive correlation was found between providing dual task education and better cognitive function for the elderly. Objective: This activity aims to introduce physiotherapy and prevent decline in cognitive function in the elderly. Method: This activity begins with identifying the problem using the interview method and giving a questionnaire, after that counseling is carried out in the form of education and providing dual task training, then in the final stage door to door monitoring and evaluation is carried out. Results: There was an increase in knowledge in the elderly after being given education to prevent decreased cognitive function disorders with dual task training. Conclusion: Providing dual task training and education can increase knowledge in the elderly.